2004
DOI: 10.1080/02841850410003969
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance evaluation of cerebral toxoplasmosis in patients with the acquired immunodeficiency syndrome

Abstract: MR diffusion, spectroscopy, and perfusion studies help in characterizing toxoplasmosis lesions and, in most cases, can be used in combination to help establish the diagnosis of toxoplasmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 12 publications
2
12
0
4
Order By: Relevance
“…These results are non-specific and consistent with different pathologies as brain lymphoma, PML, and other neoplasm such as glioblastoma, being unable to discard between these etiologies [16]. On the other hand, this metabolite pattern was very similar to the reported in brain toxoplasmosis [16,17]. This could be caused by the fact that both parasites induce inflammation and necrosis and therefore may share a similar metabolite profile.…”
Section: Discussionsupporting
confidence: 74%
“…These results are non-specific and consistent with different pathologies as brain lymphoma, PML, and other neoplasm such as glioblastoma, being unable to discard between these etiologies [16]. On the other hand, this metabolite pattern was very similar to the reported in brain toxoplasmosis [16,17]. This could be caused by the fact that both parasites induce inflammation and necrosis and therefore may share a similar metabolite profile.…”
Section: Discussionsupporting
confidence: 74%
“…L'introduzione della tecnica in diffusione con il calcolo del coefficiente di diffusione apparente (DWI-ADC) ha aggiunto utili elementi di diagnostica differenziale [3][4][5], con consensuale significativo incremento delle possibilità della RM, ma anche lo studio DWI-ADC resta gravato da problemi di specificità [6][7][8][9][10][11][12][13]. L'utilizzo della spettroscopia dell'idrogeno con RM ( 1 H-MRS) ha fornito un valido contributo nella diagnosi differenziale, ma alcuni problemi inerenti alla tecnica, i lunghi tempi di acquisizione e la relativamente scarsa diffusione sul territorio limitano l'utilizzo di questa possibilità [14][15][16].…”
Section: Methodsunclassified
“…The introduction of diffusionweighted imaging (DWI) with calculation of the apparent diffusion coefficient (ADC) has contributed useful information to the differential diagnosis [3][4][5], with a significant increase in the possibilities of MRI, although DWI is encumbered with specificity problems [6][7][8][9][10][11][12][13]. Proton MR spectroscopy ( 1 H-MRS) has also added to the differential diagnosis, although problems inherent in the technique, lengthy acquisition times and the relatively restricted diffusion of the technique limit its use [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies in lung lesions have shown significantly high peak height and increased relative flow (RF) in active tuberculoma as compared to inactive tuberculoma [24]. Infective lesions like abscess and toxoplasmosis have reduced perfusion compared to neoplastic lesions as shown by various other studies [25,26]. Thus it becomes clear from all these studies that infective lesions can be differentiated from neoplastic lesions based on perfusion studies.…”
Section: Discussionmentioning
confidence: 51%